If it's not what You are looking for type in the equation solver your own equation and let us solve it.
b+4/6=b-1/3
We simplify the equation to the form, which is simple to understand
b+4/6=b-1/3
We move all terms containing b to the left and all other terms to the right.
+1b-1b=-0.33333333333333-0.66666666666667
We simplify left and right side of the equation.
b=-1
0=-1
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| F(4)=-6x+25 | | -[10x-(3x+5)]=-4-[4(3x-4)-3x] | | n^2+22=-10n | | x+5=-4+1 | | 8(d+7)=45.6 | | h(t)=-16t^2+80t+64 | | n+3/8=6/3 | | 5x+2x-10=5x+8 | | x+2+x=22-2 | | 5/n=10/2 | | X=23+2y | | 6+x/8=6 | | -3n-27=-8n-2 | | 0.9x=0.27 | | 9=2+p/2 | | 15=8x+9 | | 15-b=4b+5 | | 1000+25h=2000 | | 19=1-3n | | 2(x+a)=36 | | Y=X^2+16+4x+16-8 | | 2250+6c=16c+50 | | (2x+3y)(x+2y)=4 | | 10+2n=-30 | | -3-27=-8-2 | | 6+3x=3a-x | | 4x^2+6x-27=0 | | 6(z+2)=5(z-7)+z | | 2r+7r=-7+8r | | -4(x+3)=7 | | 6p+10=-68 | | 64=8+(r+2) |